Advanced porous membranes with ultra-high selectivity and stability for vanadium flow batteries. Issue 2 (20th October 2015) - Yuan, Zhizhang; Duan, Yinqi; Zhang, Hongzhang; Li, Xianfeng; Zhang, Huamin; Vankelecom, Ivo
Abstract : Advanced porous membranes combining ultra-high stability and selectivity with very low cost are designed and fabricated for vanadium flow batteries. Abstract : Porous polybenzimidazole membranes with ultra-high selectivity and stability were designed and fabricated for vanadium flow batteries. The combination of the facile fabrication procedure, high performance, the low cost of the starting materials and easy up-scaling makes the PBI porous membrane currently by far the most promising candidate for vanadium flow batteries.